Forensic analysis of explosives from water samples using solid phase microextraction - gas chromatography [compact disc] - 250103 Kiu, Kee Heng (Skudai : Universiti Teknologi Malaysia, 2006)
Thesis (Sarjana Sains (Kimia)) - Universiti Teknologi Malaysia, 2006